SENSITIVITY OF THE COMMON BOVINE TICK Rhipicephalus (Boophilus) microplus TO IVERMECTIN ESTIMATED WITH THE SIGMOIDAL MAXIMUM RESPONSE MODEL OR HILL MODEL (FAVE Sección Ciencias Veterinarias, 2021)
The aim of this study was to obtain pharmacodynamics parameters to detect resistance or susceptibility of R. microplus strains to ivermectin (IVM). Two larvae samples; a susceptible strain (S) and field isolation (T) were treated with increasing concentrations of IVM using the larvae immersion technique the efficacy values measured at 24 hours were analysed with the sigmoidal maximum response so called Hill model as statistical analysis. The results obtained showed that the IVM have an all or nothing response represented by the Hill coefficient value >1 in both samples. Additionally, a low concentration effect was observed as E0 de 12.83% (S) and 9.91% (T). The field isolation larvae were susceptible to IVM in comparison with the susceptible strain by the resistance ratio (RR) which in one case was not significantly greater that one (RR50= 0.756 and RR90=1.009).
Keywords: Rhipicephalus microplus, larval immersion test, ivermectin, Hill model.